Morphogenic Studies on Derris indica (Lamk) Bennet - Ranjan, Sheela (Indian Forester, 1997)
Experimental morphogenic studies were conducted on Derris indica (Lamk.) Bennet under controlled conditions of temperature and humidity. The in-vitro culture of mature seed developed seedling. Callusing on hypocotyl, stem, leaf and cotyledons were raised under aseptic conditions on B5 medium supplemented with auxins, cytokinins and other growth substances of D. indica was also observed. Anatomical investigations were carried out to study cellular differentiation in callus induction and also to study the ontogeny of root and shoot buds, developed in cultures.